Virulence and the Role of Iron in Pseudomonas aeruginosa Infection - Bullen, J. J. (1974)
The virulence of Pseudomonas aeruginosa can be enhanced by passage in mice or rabbits. Enhanced virulence has some specificity for the host in which the passage is done. Experimental infection in the peritoneal cavity of cannulated rabbits has shown that the injection of iron compounds can lead to a rapid and fatal growth of an otherwise nonlethal dose of bacteria. In vitro the unsaturated iron-binding proteins present in the peritoneal fluid can halve the growth rate of P. aeruginosa. The restricted rate of growth is restored to normal if the iron-binding proteins are saturated with iron. Exactly the same results are achieved with purified transferrin. Both fatal and nonfatal infections with P. aeruginosa cause a sharp fall in the percentage of saturation with Fe of the plasma and peritoneal fluid. In both normal and infected animals the peritoneal fluid is invariably less saturated than the plasma. Specific antiserum not only protects against death but also against the fall in iron saturation of the plasma and peritoneal fluid. In both fatal and nonfatal infections a high proportion of viable bacteria are unphagocytized in the peritoneal cavity.